Enhancing Students’ Vocabulary Mastery Through Snowball Throwing Games at MTs GUPPI Kaluppang - Nur Afika; Sam Hermansyah; Nurul Faradillah; Sitti Aisa (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study investigated the effectiveness of the Snowball Throwing Game in enhancing seventh-grade students’ vocabulary mastery at MTs GUPPI Kaluppang. The research employed a quantitative pre-experimental one-group pre-test and post-test design. Sixteen students were selected through purposive sampling. The main instrument was a 20-item vocabulary test consisting of 10 multiple-choice items and 10 matching-word items, administered before and after the treatment. Data collection was conducted in six meetings: a pre-test, two vocabulary teaching meetings, two Snowball Throwing treatment sessions, and a post-test. The results showed that the mean score increased from 65.00 in the pre-test to 75.63 in the post-test, producing a gain of 10.63 points. The paired sample t-test yielded t(15) = -3.686 with p = 0.002, indicating a statistically significant difference between the two tests. The effect-size analysis produced Cohen’s d = 0.922 and Hedges’ g = 0.898, both indicating a large effect. These findings show that Snowball Throwing can provide an active, repeated, and collaborative vocabulary-learning experience and is effective in enhancing students’ vocabulary mastery in the context of a rural Islamic junior secondary school.